Involvement of the epidermal growth factor receptor in the modulation of multidrug resistance in human hepatocellular carcinoma cells in vitro - Hoffmann, Katrin (BioMed Central, 2011)
BACKGROUND: Hepatocellular carcinoma (HCC) is a molecular complex tumor with high intrinsic drug resistance. Recent evidence suggests an involvement of the tyrosine kinase pathway in the regulation of ATP-binding cassette protein (ABC-transport protein) mediated multidrug resistance in cancer cells. The aim of this study was to examine whether EGFR inhibition sensitizes HCCs to chemotherapy and to elucidate its mechanism. RESULTS: Chemotherapeutic treatment induces multidrug resistance and significantly increases ABC-transport protein expression and function in a time- and dose-dependent manner in HCC cells. Furthermore, cytostatic treatment increases the mRNA expression of tyrosine kinases and induces the phosphorylation of ERK. EGF activation of the tyrosine kinase pathway up-regulated the ABC-transport protein mRNA expression and enhanced the survival of resistant HCC cells. Consistent with these effects, inhibition of the EGFR using siRNA decreased the ABC-transport protein mRNA expression and inhibited the proliferation of resistant cells. Additional treatment with Gefitinib, a clinically approved EGFR inhibitor, caused a dose-dependent reversal of resistance to conventional chemotherapy. CONCLUSION: The present study demonstrates that the multidrug resistance of HCC is modulated through the EGF-activated tyrosine kinase cascade. Consequentially, the restoration of chemosensitivity by EGFR inhibition may lead towards new tailored therapies in patients with highly resistant tumors.